MENGOMENTARI TAFSIR JALÄ€LAYN: Studi Terhadap Naskah Tafsir di Jaken Pati - Umi Musyarofah (STAI AL-ANWAR SARANG, 2020)
This study examines the manuscript of the Tafsir Jalālayn in Tamansari Village, Jaken, Pati. The research method used is qualitative with a philological and historical approach. The focus of research is on the physical text or codicological aspects, as well as the study of the text. Although it is not certain who copied them(by hand), this research finds that the manuscripts were written in the late 19th century (1890 AD). The existence of comments on the main text (matan) of Tafsir Jalālayn shows that there was a learning process of interpretation as well as an attempt to provide further explanations for this tafsir that was carried out in pesantren in this area at the end of the 19th century. This study also identifies the characteristics of the text in the manuscript. First, the interlinear translation (makna gandhul) along with the grammatical code that uses Javanese language to assist students understand the content of Tafsir Jalālayn. Second, the manuscript contains Javanese vocabulary which is no longer commonly used. Third, the marginal notes in Arabic (hamish) add a broader and deeper understanding of the Quran. Hamish has five contributions to the main text, i.e: explaining in more detail the content of the verse and its tafsir; as an explanation for words that are still general; as a source of reference information on writing the hamish; as a main text corrector; and as a complementary to the translation of the main text.